2020
DOI: 10.1155/2020/5496712
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cu (II) and Cd (II) from Wastewater by Sodium Alginate Modified Materials

Abstract: Natural macromolecule adsorbing materials are alternatives for remediation of heavy metals’ polluted waters. In this study, sodium alginate composite gel (SACL) was synthesized from sodium alginate (SA), polyethylene glycol oxide (PEO), and nanomaterials to remove wastewater Cu (II) and Cd (II). The adsorption efficiency of SACL was analysed in relation to the contact time, initial concentrations of metal ions, temperature, adsorbent dosage, and solution pH. Three models, i.e., kinetic model, isothermal adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
0
15
0
2
Order By: Relevance
“…Table 2 shows the Langmuir and Freundlich isotherm data in the form of Langmuir constant (kL), maximum adsorption capacity (qm), adsorption intensity (n), and Freundlich constant (kF). Table 1 shows the Langmuir data at the Langmuir constant value (kL) of 0.070, 0.080, 0.025, 0.074, 0.040 and is in the range of 0 and 1 which identifies a suitable system for the adsorption process (Mishra et al, 2020;Zhao et al, 2020). The qm data shows the value of large adsorption capacity on the adsorbent of LDH-Hc composite materials (Ni/Al-Hc, Cu/Al-Hc, Zn/Al-Hc) reaching 144.928 mg/g, 175.439 mg/g, 217.910 mg/g while rambutan peel precursors and Hc had lower adsorption capacities of 43.860 mg/g and 49.286 mg/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows the Langmuir and Freundlich isotherm data in the form of Langmuir constant (kL), maximum adsorption capacity (qm), adsorption intensity (n), and Freundlich constant (kF). Table 1 shows the Langmuir data at the Langmuir constant value (kL) of 0.070, 0.080, 0.025, 0.074, 0.040 and is in the range of 0 and 1 which identifies a suitable system for the adsorption process (Mishra et al, 2020;Zhao et al, 2020). The qm data shows the value of large adsorption capacity on the adsorbent of LDH-Hc composite materials (Ni/Al-Hc, Cu/Al-Hc, Zn/Al-Hc) reaching 144.928 mg/g, 175.439 mg/g, 217.910 mg/g while rambutan peel precursors and Hc had lower adsorption capacities of 43.860 mg/g and 49.286 mg/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The Q e values of this study were reported as 53.29 for Cu(II) and 129.28 for Ni(II). Zhao et al developed sodium alginate-polyethylene glycol oxide-nano materials based composite gels for the removal of heavy metal ions such as Cu(II) and Cd 2+ from polluted water [ 52 ]. In this study, the fabricated materials showed the adsorption capacity (Q m ) for Cu(II) and Cd(II) as 6.78 and 3.43 with the removal rates 96.8% (Cu(II)) and 78% (Cd(II)).…”
Section: Resultsmentioning
confidence: 99%
“…The Qe values of this study were reported as 53.29 for Cu(II) and 129.28 for Ni(II). Zhao et al developed sodium alginate-polyethylene glycol oxide-nano materials based composite gels for the removal of heavy metal ions such as Cu(II) and Cd 2+ from polluted water [52].…”
Section: Ion Exchange Capacity Oxidative Stability Proton Conductivity and Methanol Permeability Studiesmentioning
confidence: 99%
“…For example, the removal of metal ions is incomplete, requiring higher reagents and energy, producing toxic sludge or other wastes, and taking a long time to desorb [3]. Adsorption is considered as an effective method to treat heavy metal pollution in wastewater [4]. The principle of adsorption method is to use the porous structure of adsorbent and the physical properties of large surface area to adsorb pollutants in water, to achieve the purpose of removing heavy metals in water [5].…”
Section: Introductionmentioning
confidence: 99%